Using cylindrical implosions to investigate hydrodynamic instabilities in convergent geometry - J. P. Sauppe (Matter and Radiation at Extremes, 2019)
Hydrodynamic instabilities such as the Rayleigh–Taylor (RT) and Richtmyer–Meshkov instabilities disrupt inertial confinement fusion (ICF) implosions through the growth of 3D perturbations. Growth of these 3D imperfections at the interfaces of an ICF capsule during implosion lead to mixing between materials that is detrimental to performance. These instabilities have been studied extensively in planar geometry, but such experiments lack the effects of convergence in spherical implosions. While several studies have been performed in spherical geometry, these often lack a direct means to measure perturbation growth. Experiments in cylindrical geometry include convergence effects while maintaining direct diagnostic access. Although cylinders have less compression than spheres, they do provide an excellent platform to validate modeling for convergent geometries. The problem with previous cylindrical implosion experiments was that the convergence ratios were limited to ∼4. With the National Ignition Facility (NIF), larger cylindrical targets can be driven to convergences of 10–15 while maintaining a large enough final diameter to measure perturbation growth. This paper reviews the design process used to both benchmark radiation hydrodynamics codes and enable 1D post-processed simulations to explore design space to separate compression effects from acceleration/deceleration RT instability. Results from 1D simulations suggest that cylindrical implosions on the NIF can produce high-convergence experiments to validate RT instability growth for ICF implosions.